Untersuchungen zum Gehalt von arbeitsmedizinisch-toxikologisch relevanten Inhaltsstoffen in Bitumen und Bitumen-Emissionen sowie human-experimentelle Versuche zu deren dermalen Resorption - Walter, Dirk; Justus Liebig University Giessen (My University, 2006)
Durch human-experimentelle Untersuchungen in einer Versuchskammer konnte die Frage einer dermalen Resorption nach Exposition gegenüber Aerosolen und Dämpfen von Bitumen beantwortet werden. Zur Generierung der Bitumen-Emissionen wurde handelsübliches Bitumen B 65 eingesetzt. Die Luftprobenahme und analyse erfasste getrennt die Aerosole und die dampfförmigen Emissionsanteile sowie die darin enthaltenen polycyclischen aromatischen Kohlenwasserstoffe (PAH). Exponiert wurden zehn nicht rauchende, männliche Probanden mit und zusätzlich zwei der zehn Probanden ohne gebläseunterstützte Atemschutzmaske über acht Stunden. Die Quantifizierung der dermalen bzw. der kombinierten inhalativ/dermalen Resorption orientierte sich am Biomonitoring der PAH-Metabolite von Pyren, Chrysen und Phenanthren im Harn. Die gemessenen Bitumen-Emissionen lagen im Mittel bei 20,4 mg/m3 mit einem dampfförmigen Anteil von ca. 88 %. Im Fall der beiden dermal bzw. inhalativ/dermal belasteten Probanden betrug die alleinige dermale Resorption ~57 % für Pyren und Chrysen und für Phenanthren etwa 50 %.

Human exposure to vapour and aerosols produced during processing of hot bitumen in an experimental chamber were performed to comment question of possible absorption of this emissions through skin. Commercial bitumen B 65 was used to generate bitumen emissions in a specially made evaporator at 200 °C in an exposure chamber of about 17 m³. The system used for air sampling and analysis permitted separate evaluation of aerosols and vapours as well as polycyclic aromatic hydrocarbon (PAH) content in each of this matter. In each case 10 male nonsmokers were exposed for 8 h with and in addition two of them without a blower-supported breath mask. 4 h after starting exposure was interrupted by a pause of 45 min when the proband stood outside of the chamber. Quantification of percutaneous and combined inhaled as percutaneous absorption, respectively, was related to biological monitoring of PAH metabolites of hydroxy-pyrene, -chrysene, and -phenanthrene in urine. The bitumen emissions were determined to be on average at 20.4 mg/m3 The proportion of aerosols compared with vapour amounted to 1.0 and 7.2. The PAH concentrations measured in this fractions showed a similar trend. The PAH with high molecular weight are existent in aerosols whereas volatile PAH remained in vapour phase. The maximum of PAH excretion in urine could be observed about 8 to 14h after start of exposure. On average concentrations ranged from factor 1.4 to 3.7 higher compared with reference values in urine measured before starting experiment. The two subjects stressed by inhalation and percutaneous contact with bitumen showed PAH absorption values through skin of approximately 57 % for pyrene and chrysene and about 50 % for phenanthrene. The measurement procedure for bitumen emissions in workplaces has to take into account different state of aggregation of bitumen emissions. In case of PAH at workplace absorption through skin can make a significant contribution to internal exposure to employee so that individual exposures can be determined and evaluated only by biological monitoring.
Standardized investigation of the percutaneous absorption of bitumen emissions in man
Keywords: Standardisierte Expositionen; Biological Monitoring; Standardized human exposures; biological monitoring; ddc:610